Estudo de micropartículas na pré-eclâmpsia grave - Fabiana Kalina Marques (2012)
Preeclampsia (PE) is a multi-system disorder, characterized by hypertension and proteinuria, occurring after the twentieth week of pregnancy. Despite intensive research, PE is still one of the leading causes of maternal mortality, and reliable screening tests or effective treatments of this disease have yet to be discovered. The most common procedure is to deliver the baby and the placenta, often prematurely, in the interest of providing the most appropriate conditions for the baby or the mother. Therefore, improving the overall understanding of the role of microparticles in PE may well be useful for new clinical diagnoses and therapeutic approaches. Microparticles (MPs) are small vesicles released after cell activation or apoptosis, which contain membrane proteins that are characteristic of the original parent cell. MPs have been proven to play key roles in thrombosis, inflammation, and angiogenesis, as well as to mediate cell-cell communication by transferring mRNAs and microRNA from the cell of origin to target cells. It has been suggest that MPs, mainly placenta-derived syncytiotrophoblast microparticles (STBMs), may well play an important role in the pathogenesis of PE.